2023
DOI: 10.3390/su151612295
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Streamflow Modeling in the Godavari Basin with CMIP6 Dataset

Abstract: Accurate streamflow modeling is crucial for effective water resource management. This study used five machine learning models (support vector regressor (SVR), random forest (RF), M5-pruned model (M5P), multilayer perceptron (MLP), and linear regression (LR)) to simulate one-day-ahead streamflow in the Pranhita subbasin (Godavari basin), India, from 1993 to 2014. Input parameters were selected using correlation and pairwise correlation attribution evaluation methods, incorporating a two-day lag of streamflow, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…They reported that RF model outperformed the other models in the prediction model. Saravanan et al (2023) modelled one‐day‐ahead streamflow in the Godavari basin of India using linear regression (LR), SVR, RF, multilayer perceptron (MLP) and M5‐pruned model (M5P). Both RF and M5P showed promising results on supplied CMIP6 datasets.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that RF model outperformed the other models in the prediction model. Saravanan et al (2023) modelled one‐day‐ahead streamflow in the Godavari basin of India using linear regression (LR), SVR, RF, multilayer perceptron (MLP) and M5‐pruned model (M5P). Both RF and M5P showed promising results on supplied CMIP6 datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Since the decision trees in the RF are generated independently from random samples, there is a low association between the trees. Afterward, voting takes place using the classifications generated by each tree, and the class with the most votes is used to predict the presented sample [27]. 4.…”
mentioning
confidence: 99%